Amari and the night brothers - Alston, B. B. (Balzer + Bray, 2022)
Amari Peters has always believed that her missing brother, Quinton, is still alive somewhere. When she discovers a ticking briefcase in his closet, Amari learns about the existence of the Bureau of Supernatural Affairs, a secret organization that deals with magicians, fairies, aliens, and other supernatural creatures. Amari accepts an invitation to join the Bureau of Supernatural Affairs but finds herself out of her depth and competing against other kids who have known about magic their entire lives. But Amari is determined to succeed in order to find out the truth about what happened to her brother.